Novel Minimal Invasive Technique and Cases Report: Arthroscopic Anchor Repair of Medial Patellofemoral Ligament on Recurrent Patella Dislocation - Yun-Che Tsai; Cheng-Chang Lu; Yu-Ting Shen; Yu-Chuan Lin; Ping-Cheng Liu; Paul Pei-Hsi Chou (Formosan Journal of Musculoskeletal Disorders)
This article describes a minimal invasive surgical (MIS) technique for arthroscopic repair of medial patellofemoral ligament partial tear on patella dislocation with suture anchor. Patella dislocation usually complicated with medial patellofemoral ligament (MPFL) injury, which lead to lateral subluxation or dislocation. MPFL acts as an important knee stabilizer to prevent lateralized force on the patellofemoral joint. Currently, surgical management includes various kinds of open procedures for repairing or reconstructing ligament. We had developed a MIS technique for arthroscopic repair on two patients with partial MPFL tear and recurrent patella subluxation/dislocation episodes. The radiographic and clinical results of both patients revealed restoration of full activity without patella subluxation after 12 months’ follow-up. We believed that this MIS technique prevent soft tissue from stripping and restore patella stability with good satisfaction.